The Influence of Training Participation and Work Discipline on Employee Performance - Yhonanda Harsono (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2023)
This study aims to analyze the effect of training participation and work discipline on employee performance simultaneously. The sample population in this study were employees of PT. Ciomas Adisatwa in the marketing department, totaling 52 people. This type of research is associative quantitative because it asks the relationship between two or more variables. The analytical method used is Multiple Linear Regression. The instrument used was a questionnaire to collect data from job training, work discipline, and employee performance variables. Data analysis techniques used are Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis Test, Multiple Correlation Coefficient Test, Coefficient of Determination Test, t test, and F test. Based on the results of the t test, it can be obtained that the value of tcount < ttable or (1.390 < 1.675), this is also reinforced by a significance value of 0.000 < 0.05. Thus, Ho1 is accepted and Ha1 is rejected. This shows that there is no positive and significant effect between Training Participation (X1) on employee performance (Y) at PT Ciomas Adisatwa Bogor. Thus, Ho2 is rejected and Ha2 is accepted, this shows that there is a positive and significant influence between work discipline (X2) on employee performance (Y) PT. Ciomas Adisatwa Bogor. The value of the correlation coefficient or the level of relationship between the independent variable and the related variable is 0.994 where the value is in the interval 0.800-1.000, which means that the variables of training participation (X1) and work discipline (X2) have a very strong relationship to employee performance (Y).